Modeling the Dynamics of The Second Wave of Corona Virus (COVID-19) Pandemic in Nigeria - Wusu, Ashiribo Senapon; Olabanjo, Olusola; Akanbi, Moses; Aribisala, Benjamin (Transactions on Engineering and Computing Sciences, 2021)
The resurgence of the dreaded coronavirus (COVID-19) pandemic is rapidly taking its toll across the globe. Like other nations of the world, the need to flatten the curves is now the top priority of both governmental and non-governmental organisations in Nigeria. Understanding the dynamics of the disease is crucial in making suitable preventive policies that will slow the spread and ultimately flatten the curves. In this work, a compartmental--based model for analysing the dynamics of the pandemic second wave in Nigeria is presented. The model is fitted to the available data accessible on the Wolfram Data Repository and the parameter values estimated with the use of Quasi--Newton algorithm. Efficiency of the current control policies is measured and projections of the dynamics of the disease in coming days are made. Recommendations on how to manage the resurgence of the disease are also suggested.